Women Entrepreneurship as the Way of Economic Development: An Empirical Study of with Reference to South Indian Statess (International Journal of Innovative Research in Engineering & Management, 2022)
The role of girls entrepreneurs has  changed over the years in the world. Participation and their  importance are commendable in the country’s economic  growth and development. the planet Development Report,  2021represents that ladies owned businesses show great  potential source of future for economic growth and job  creation. Therefore, many initiatives are started by United  Nations to promote and motivate women entrepreneurship  in developing and under developed countries such as India. India has also supported many ladies entrepreneurs by  providing loans and advances, helping them to determine  their business, making them self- sufficient by providing  vocational skills, and creating many roles for other  women in the respective areas. These opportunities are  need-based in India, and lots of factors are driving these  forces. this text studies these aspects in four parts; the first  part deals with growth of women entrepreneurs in south  India, the second part studies tapping this growth in  financing women entrepreneurs which may be a major  problem of failure in their businesses third deals with the  role of self help groups (SHGs) in promoting finances and  empowering them through capacity building programmes,  and therefore the fourth part deals with future policies of  the government providing conducive environment for their  business.
Keywords: Women Entrepreneurs; Financing; Self Help Groups; Government Policies